Academic Performance and Satisfaction of Student-Directed Learning in Online Education Among Multidisciplinary Undergraduate Students: A Retrospective Comparative Study - Basma Al Yazeedi PhD; Zeinab Al Azri PhD; Lina Shakman MSN; Safiya Al Shidhani MED; Maryam Al Kharusi BSc (SAGE Open Nursing)
Introduction The outcomes of student-directed learning (SDL) compared to teacher-directed learning (TDL) in online education is yet to be established. Objective(s) This study compared the academic performance outcomes between students enrolled in SDL online course with those enrolled in TDL online course. Additionally, the researchers assessed student satisfaction with the educational design, communication and interaction, and assessment and evaluation of the SDL online course. Method A retrospective comparative design study was conducted. The researchers studied two groups of multidisciplinary students enrolled in two different classes (classes A and B) of the Physical and Psychological Child Health course. A complete enumeration sampling method was followed, where students in class A received the SDL, while students in class B had the TDL. The study outcome measured was students’ grades in the first (Week 3), second (Week 6), and final (Week 8) exams, reflecting the students’ academic performance in the taught course. Additionally, students’ satisfaction with the SDL course was assessed using a 17-item self-reported questionnaire. Descriptive and Mann-Whitney U nonparametric test were used. Significance was set at less than .05. Results Data from 118 students, 63 in the SDL group and 55 in the TDL group, were analyzed. Students in the SDL class demonstrated notably higher final exam scores than students in the TDL class ( p  = .02). Yet after removal of outliers, the difference was not significant ( p  = .08). Widespread satisfaction was evident with the SDL course, with an overall satisfaction rate of 85%. The satisfaction rate for educational design, communication and interaction, and assessment and evaluation was 88.4%, 78.8%, and 86.4%, respectively. Conclusion Applying SDL in online education has strong potentials to improve learning outcomes, while at the same time satisfy students’ learning needs. Future research may focus on investigating the integration of practical components in student-directed online education.